Hepatitis B antibody titers in Indonesian adolescents who received the primary hepatitis B vaccine during infancy - Hartono Gunardi; Adra Firmansyah; Sri Rezeki S Harun; Sudigdo Sastroasmoro (Indonesian Pediatric Society, 2013)
Backgi-ound Hepatitis B (HB) has been classified as moderate-tohighlyendemic in Indonesia. HB vaccination, the most effectivemethod to prevent HB viral transmission, induces protectiveantibodies against HB surface antigen (anti-HBs). However, theseantibodies decline in titer over time. Studies on the duration ofprotection and the prevalence of n on-responders in Indonesianadolescents have been limited.Objectives To determine anti-HBs titers in 15-17-year oldIndonesian adolescents given primary HB vaccine during infancyand the prevalence of non-responders after a HB vaccine boosterdosage.Methods This cross-sectional study was performed from Februaryto September 2008 on adolescents aged 15-17 years in threesenior high schools in Jakarta who received complete primary HBvaccines during infancy, based on parents' recall. Investigationsincluded HB vaccination history, anthropometric measurements,and blood tests for anti-HBs before and 4-6 weeks after a boosterdose ofHB vaccine.Results Of 94 subjects, 35 had protective anti-HBs and 59 hadundetectable anti-HBs. A booster dose was administered to 5 8 of then on-protected subjects, of which 33 showed anamnestic responses.However, 25 subjects failed to generate protective anti-HBs. Takinginto consideration the adolescents with protective anti-HBs beforeand after the booster dose, serologic protection was demonstratedin 73%. Non-responder prevalence was 27%. The high prevalenceof non-responders may indicate bias of parents' recall.Conclusion Protective anti-HBs is detected in less than half ofIndonesian adolescents given primary HB vaccine during infancy.Following booster dosage, anamnestic responses are n oted in onethirdof subjects. The prevalence of non-responders is 27%, butconfirmation with further study is needed.